MENCEGAH PENYEBARAN PAHAM RADIKALISME PADA SEKOLAH - Noermala Sary (Sekolah Pasca Sarjana IAIN Bengkulu, 2017)
The problem discussed in this thesis is how the strategy of PAI clusters teacher in preventing the spread of radicalism in MAN 1 of Bengkulu City, and its supporting and inhibiting factors. The purpose of this study intends to describe the strategy of PAI teacher teachers in preventing the spread of radicalism in Madrasah AliyahNegeri1 Bengkulu city, describing the supporting factors and obstacles of PAI teachers in preventing the spread of radicalism in Madrasah AliyahNegeri 1 Bengkulu City. The method used is descriptive qualitative with the type of field research (field research). Data collection techniques: observation, interviews, and documentation. Data analysis techniques: data reduction, data display and conclusion. The result of the research shows that the strategy of PAI teacher in preventing the spread of radicalism in MAN 1 is divided into two types: the strategy in the learning process in the classroom by using the active learning method and the Qur’an method of learning, and the process Learning outside the classroom is: by holding various religious activities, forming a team of worship in school, in cooperation with the police such as Sat. Bintal, and Sat. Binmas, in cooperation with the provincial kemenag, held workshops and religious socialization in schools. Supporting factors in the implementation of prevention strategies of the spread of radicalism in schools is a sufficient means of infrastructure both from learning resources, the allocation of study time and teachers of the PAI family. Inhibiting factors are misuse of informatics (IT) technology by students, the absence of special programs in preventing the school’s radical hazards, the lack of parental support for school policies, the lack of cooperation between schools with guardians, teachers with guardians, and the lack of Cooperation among teachers.